Trace gluten contamination may play a role in mucosal and clinical recovery in a subgroup of diet-adherent non-responsive celiac disease patients - Hollon, Justin R (BioMed Central, 2013)
BACKGROUND: Patients with persistent symptoms and/or villous atrophy despite strict adherence to a gluten-free diet (GFD) have non-responsive celiac disease (NRCD). A subset of these patients has refractory celiac disease (RCD), yet some NRCD patients may simply be reacting to gluten cross-contamination. Here we describe the effects of a 3-6 month diet of whole, unprocessed foods, termed the Gluten Contamination Elimination Diet (GCED), on NRCD. We aim to demonstrate that this diet reclassifies the majority of patients thought to have RCD type 1 (RCD1). METHODS: We reviewed the records of all GFD-adherent NRCD patients cared for in our celiac center from 2005-2011 who were documented to have started the GCED. Response to the GCED was defined as being asymptomatic after the diet, with normal villous architecture on repeat biopsy, if performed. RESULTS: Prior to the GCED, all patients were interviewed by an experienced dietitian and no sources of hidden gluten ingestion were identified. 17 patients completed the GCED; 15 were female (88%). Median age at start of the GCED was 42 years (range 6-73). Fourteen patients (82%) responded to the GCED. Six patients met criteria for RCD prior to the GCED; 5 (83%) were asymptomatic after the GCED and no longer meet RCD criteria. Of the 14 patients who responded to the GCED, 11 (79%) successfully returned to a traditional GFD without resurgence of symptoms. CONCLUSIONS: The GCED may be an effective therapeutic option for GFD-adherent NRCD patients. Response to this diet identifies a subgroup of patients, previously classified as RCD1, that is not truly refractory to dietary treatment. Preventing an inaccurate diagnosis of RCD1 avoids immunotherapy. Most patients are able to return to a traditional GFD without return of symptoms.